Geometric and Non-Geometric Backgrounds of String Theory - Moutsopoulos, George (The University of Edinburgh, 2008)
This thesis explores the geometry of string theory backgrounds and the nongeometric features of string theory that arise due to T-duality. For this reason, it is divided into two complementary parts. Part I deals with the superalgebras of symmetries of string theory and M-theory backgrounds, the so-called Killing superalgebras. It is shown that one can define a Lie superalgebra consisting of the infinitesimal field-preserving isometries and the supersymmetries of the background. We also explore the extension of a Killing superalgebra with brane charges. Part II deals with non-geometric backgrounds. In particular, we adopt the framework of the doubled geometry, also known as the doubled torus. We analyze the hamiltonian dynamics of the system and quantize a model T-fold. Finally we extended the doubled torus system to include worldsheet supersymmetry. Throughout part II, we focus on the equivalence, classical and quantum, of the doubled formalism with the conventional formulation.
Keywords: Mathematics; String Theory